The Effect of Production Costs on Weaving Craftsmen's Income During the Covid 19 Pandemic - Ramli, Muh; Ichsan, Nursyamsi; Pirman, Pirman (Jurnal Ekonomi Balance, 2022)
The purpose of this research was to determine the effect of production costs on the income of weaving craftsmen during the COVID-19 pandemic (a case study of Bira Village, Bonto Bahari District, Bulukumba Regency). This research area was a well-known weaving craftsman area in South Sulawesi with a total of weaving craftsmen in Bira Village, which has four hamlets, namely Pungkarese Hamlet, Birakeke Hamlet, Tanetang Hamlet, and Liukangloe Hamlet. In total, in the four hamlets, there were 105 weaving craftsmen, but in this research, the sample was carried out using a formula with an error limit of 10%, so that the sample used was 52 people. In terms of data collection for this research, method of observation, questionnaire technique, and documentation were used. This research was conducted from May to July 2022. The type of research method applied in this research was descriptive research using quantitative. The analytical method was demonstrated by describing the impact of production costs on the income of weaving craftsmen in Bira Village, Bonto Bahari District, Bulukumba Regency. This test was assisted by the programs (SPSS), Simple Linear Regression Analysis, Coefficient of Determination (R2), T-Test. The results of the hypothesis test proved that the results of a simple linear regression test obtained Y = 9.917 + 0.729x, means that the constant value was 9.917 with a regression coefficient of 0.729, indicating that the direction of the influence of the variable X on Y  was positive and the value sig0.000 <0,05, revealing that production costs have a significant effect on the income of weaving craftsmen during the COVID-19 pandemic in Bira Village, Bonto Bahari District, Bulukumba Regency. The influence of the raw material inventory control variable on the production process was 56.7%, while the remaining 43.3% was influenced by other objects